ANTIFOULING AND ANTICORROSIVE PREVENTION WITH CERAMIC COATINGS ON OFFSHORE STRUCTURES FOR RENEWABLE ENERGY (Proceedings of the European Wave and Tidal Energy Conference, 2023)
In the past, ships, port facilities and offshore platforms dedicated to the exploitation of fossil resources were the only man-made structures that were exposed to seawater, currently the exposed structures are extended to all those used in the field of renewable ocean energy sources, such as waves, tidal flows or oceans streaming and offshore wind energy. Therefore, this study highlights the need for offshore structures to consider the choice of ceramic coatings in the field of surface treatment and marine corrosion control without neglecting another of the main problems that affects structures in contact with seawater, which is the phenomenon known as biofouling. Corrosion is a major problem in offshore environments due to extreme operating conditions and the presence of aggressive corrosive elements. The corrosion resistance can represent the difference between trouble-free long-term operation and costly downtime. On the other hand, biofouling, which is defined as the undesirable phenomenon of adherence and accumulation of biotic deposits on an artificial surface that is submerged or in contact with sea water, can cause variations in the weight distribution of a floating structure, affecting its stability. In addition, biofouling leads to corrosion in the same way that corrosion leads to biofouling, so both factors are studied in parallel.This study evaluated differences in the total of seawater biofouling attached on coated paints and ceramic coatings in carbon steel for offshore structures. All three different ceramic coatings were made of incorporating active ceramic particles against biofouling as titanium, cobalt and manganese. In this study, the ASTM-D3623 test method, for the protection of submerged marine structures, was used. This method covered the procedure for testing antifouling coatings exposed for a period of two year at an immersion site with a high biological activity in shallow marine environments.The results of the investigation showed that the cobalt-based coating had the best antifouling properties at the end of the experimentation, although there was no significant difference in the biofouling attached during the two years of exposure, but great differences were shown with respect to the antifouling paints. Biofouling adhesion resistance was greatest when a coating thickness of 217 μm was used and when the substrate surface roughness (Ra) was 0.245 µm. The results indicated up to more 30% total area covered by biofouling in paint coatings than ceramic coatings. On the other hand, the results showed a progressive degradation of the antifouling paint coatings, which meant an exponential increase of biofouling adhered to the samples, but not in ceramic coatings during the two years experiments.